The Influence of Teacher Awareness and Achievement of Learning Islamic Religious Education on The Morality of Learners - Budi Apriandi (Ruhama : Islamic Education Journal, 2021)
This study aims to examine the influence of teacher awareness and learning achievements of Islamic Religious Education on the morality of public high school students during covid-19. The number of research samples as many as 202 students and sampling techniques using proportionate stratified random sampling techniques. The first and second hypotheses were tested with simple regression techniques and the third used double regression. As for the calculation of author data using SPSS 23 program. First, there is a significant influence on the morality of PAI Teachers on the morality of public high school students during the covid-19 period. Based on the acquisition of Fhitung (140,707) greater than Ftabel to the real level of α = 0.05 and α = 0.01 (Fcount = 140.707 > Ftable = 3, 89 and Fcount = 140.707 > Ftable = 6.76) and Tcount> (9,133 > 1,789 > 2,681) at α = 0.05 and α = 0.01, The coefficient of determination is 0.413. ( 41.3% ). Second, there is a significant influence on the learning achievements of PAI there are morals of students of SMA. Based on the acquisition of Fcount (8,164) greater than Ftable to the real level α = 0.05 (Fcount = 8.164 > Ftable = 3, 89 and Fcount = 8.164 > Ftable = 6.76 and also TCount>Ttable (7.641 > 2.353 or 7.641 > 2.681) at α = 0.05 and α = 0.01. The coefficient of determination is 0.039. ( 3,9 % ). Third, there is a significant influence of teacher's awareness PAI jointly on the students of SMA Negeri Based on the acquisition of Fcount (35,173) greater than Ftable to the real level α = 0.05 and α = 0.01 (Fcalculate = 35.173 > Ftable = 3.04 and Fcount = 35.173 > Ftable = 4.71) and also tcount acquisition> (5,035 > 1,860 or 5,035>2.89) and tcount> variable learning achievement (5.03 5 > 2,353 or 5,035 > 4,541) at α = 0.05 and α = 0.01, The coefficient of determination was 0.261 (26.1% ).